Temporal differences in food abundance promote coexistence between two congeneric passerines. - Veen, T; Sheldon, B; Weissing, F; Visser, M; Qvarnström, A; Saetre, G (2010)
Many related species share the same environment and utilize similar resources. This is surprising because based on the principle of competitive exclusion one would predict that the superior competitor would drive the other species to extinction; coexistence is only predicted if interspecific competition is weaker than intraspecific competition. Interspecific competition is frequently reduced by differential resource use, resulting in habitat segregation. In this paper, we use the closely related collared and pied flycatcher to assess the potential of habitat differences to affect interspecific competition through a different mechanism, namely by generating temporal differences in availability of similar food resources between the two species. We found that the tree species composition of the breeding territories of the two species differed, mainly by a higher abundance of coniferous species around nest-boxes occupied by pied flycatchers. The temporal availability of caterpillars was measured using frass traps under four deciduous and two coniferous tree species. Deciduous tree species showed an early and narrow peak in abundance, which contrasted with the steady increase in caterpillar abundance in the coniferous tree species through the season. We subsequently calculated the predicted total caterpillar biomass available in each flycatcher territory. This differed between the species, with biomass decreasing more slowly in pied flycatcher territories. Caterpillar biomass is strongly correlated with the reproductive success of collared flycatchers, but much less so with pied flycatchers. However, caterpillar availability can only partly explain the differences in seasonal decline of reproductive success between the two species; we discuss additional factors that may contribute to this species difference. Overall, our results are consistent with the suggestion that minor habitat differences between these two species may contribute to promoting their coexistence.